2018
DOI: 10.1111/ijfs.13799
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobia activity of garlic (Allium sativum L.) and holy basil (Ocimum sanctum L.) essential oils applied by liquid vs. vapour phases

Abstract: Summary Antimicrobial activity of garlic (Allium sativum L.) and holy basil (Ocimum sanctum L.) essential oils (GEO and HBEO, respectively) was evaluated in liquid vs. vapour phases. Diallyl disulphide and diallyl trisulphide in GEO while eugenol, caryophyllene and methyl eugenol in HBEO were predominant active compounds. Individually, GEO was highly effective in the vapour phase, showing the greatest antimicrobial activity (P ≤ 0.05) against Bacillus cereus and Staphylococcus aureus with complete inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…As noted above (Goñi et al, ), Salmonella behaved very differently than did E. coli O157:H7, toward vaporized cinnamon and clove EOs. Torpol, Wiriyacharee, Sriwattana, Sangsuwan, and Prinyawiwatkul () found that Salmonella was significantly inhibited by garlic EO, both by vapor and disc diffusion contact methods, whereas E. coli O157:H7 was unaffected. Nedorostova, Kloucek, Kokoska, Stolcova, and Pulkrabek () showed that the responses of E. coli O157:H7 and Salmonella Enteritidis varied depending on the EO vapor tested.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above (Goñi et al, ), Salmonella behaved very differently than did E. coli O157:H7, toward vaporized cinnamon and clove EOs. Torpol, Wiriyacharee, Sriwattana, Sangsuwan, and Prinyawiwatkul () found that Salmonella was significantly inhibited by garlic EO, both by vapor and disc diffusion contact methods, whereas E. coli O157:H7 was unaffected. Nedorostova, Kloucek, Kokoska, Stolcova, and Pulkrabek () showed that the responses of E. coli O157:H7 and Salmonella Enteritidis varied depending on the EO vapor tested.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (Torpol et al ., ) showed that HBEO contained eugenol (49.87%) and caryophyllene (4.96%) as main components, however, DADS (31.67%), DATS (31.56%) and DATTS (13.48%) were the major fractions in GEO. Consequently, the combined GEO+HBEO (1:1 v/v) was potentially a strong antimicrobial inhibitor because HBEO contributed a large percentage of eugenol and caryophyllene as inhibitory agents, and DATTS was a key fraction of GEO.…”
Section: Resultsmentioning
confidence: 99%
“…After extraction at 25 °C for 30 min, SPME fibre with adsorbed volatile components was inserted into the injection port of a GC–MS instrument (model GC‐7890A, Hewlett‐Packard, Santa Clara, CA, USA) equipped with a DB‐5 capillary column (30 m, 0.25 mm I.D., 0.25 μm film thickness) and MS detector (MSD 5975C), and the volatiles identified and quantified according to the method of Torpol et al . ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations